Improving Students’ Participation and Performance in Building Quantities through Think-Pair-Share Cooperative Learning - Fathin Amirah Ismail; Jabaidah Bungsu; Masitah Shahrill (Universitas Pendidikan Indonesia (UPI), 2023)
The Think-Pair-Share (TPS) cooperative learning is associated with high student participation and performance in various subjects. However, research focusing on this direction in Vocational and Technical Education (VTE) is not widespread. This mixed method with an action research approach investigated the effectiveness of TPS cooperative learning in improving student participation and performance in building quantities. It also explored the perceptions of students about TPS cooperative learning intervention. Convenience sampling was used to select 24 students from one of the VTE institutions in Brunei Darussalam. Data were collected through a pre-test, a post-test, interviews, and observations; and analyzed with a paired sample-test, frequency and percentage counts, and thematic analysis. The results showed that TPS cooperative learning improved student performance and participation. It encouraged creativity, collaboration, active learning, and motivation, which are conduits to high performance and participation. Although the implementation of TPS cooperative learning comes with some challenges, it can be an effective tool to improve student performance and participation in VTE. Its key features, such as teamwork, critical thinking, and problem-solving skills, may contribute to nurturing the soft skills needed in VTE. Also given are the recommendations for the effective implementation of TPS cooperative learning in VTE.